CD4+CD45RBHi T cell transfer induced colitis in mice is accompanied by osteopenia which is treatable with recombinant human osteoprotegerin. Issue 1 (10th December 2004) - Byrne, F R; Morony, S; Warmington, K; Geng, Z; Brown, H L; Flores, S A; Fiorino, M; Yin, S L; Hill, D; Porkess, V; Duryea, D; Pretorius, J K; et al.
Abstract : Background and aims: Transfer of CD4 + CD45RB Hi T cells into semi syngeneic immunodeficient mice represents a model of inflammatory bowel disease (IBD). As patients with IBD often suffer from osteopenia, we studied if this T cell transfer in mice results in osteopenia in addition to colitis, and if treatment with osteoprotegerin (OPG) has effects on the bone mineral density of T cell transferred mice. We also investigated whether osteopenia was due to malabsorption as a result of a dysregulated digestive tract or as a consequence of the inflammatory process. Methods: CD4 + CD45RB Hi or CD4 + CD45RB Lo T cells (4×10 5 ) were sorted from CB6F1 and transferred into C.B.17 scid/scid mice. Recipient mice were treated with human IgG1 Fc (control) or Fc-OPG three times per week in a prophylactic regimen as well as a therapeutic regimen (after 10% body weight loss) and were evaluated for osteopenia and colitis. Results: Mice that received CD4 + CD45RB Hi T cells developed osteopenia (as indicated by decreased bone density accompanied by decreased osteoblasts and increased osteoclasts) and colitis (as indicated by histological changes in the large intestine). Mice that received CD4 + CD45RB Lo T cells developed neither osteopenia nor colitis. All animals consumed, on average, the same amount of food and water over the course of the study. Prophylactic treatment with Fc-OPG increased bone density in mice that received either CD4 + CD45RB Hi or CD4 + CD45RB Lo T cells but had no effects on the gastrointestinal tract. Fc-OPG treatment of osteopenic mice with established IBD caused the normalisation of bone density. Osteopenia in CD4 + CD45RB Hi T cell recipients was accompanied by hypoparathyroidism that was partially normalised by treatment with Fc-OPG. CD4 + CD45RB Hi T cell recipients also had a bone marrow inflammatory cell infiltrate expressing tumour necrosis factor α which was unaffected by treatment with Fc-OPG. Conclusions: CD4 + CD45RB Hi T cell transfer results in osteopenia in addition to colitis. Evidence suggests that this osteopenia was induced by inflammatory cell infiltration and not by malabsorption of calcium. Recombinant human osteoprotegerin effectively treated the osteopenia. OPG may be a useful therapeutic option for treating osteopenia in patients with IBD.